2012
DOI: 10.1096/fj.12-218073
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic exposure to propylthiouracil disrupts left‐right patterning inXenopusembryos

Abstract: Antithyroid medications are the preferred therapy for the treatment of Graves' disease during pregnancy. Propylthiouracil (PTU) is favored over methimazole (MMI) due to potential teratogenic concerns with MMI. This study was to determine the teratogenic potential of MMI and PTU using a validated Xenopus tropicalis embryo model. Embryos were exposed to 1 mM PTU (EC(50)=0.88 mM), 1 mM MMI, or vehicle control (water) from stages 2 to 45. Treated embryos were examined for gross morphological defects, ciliary funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…When Xenopus embryos were treated very early during embryogenesis with MMI, no adverse effects were observed (van Veenendaal et al, 2013). Yet, PTU-treated embryos manifested heterotaxy defects, and PTU was shown to directly adversely affect ciliary movement (van Veenendaal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When Xenopus embryos were treated very early during embryogenesis with MMI, no adverse effects were observed (van Veenendaal et al, 2013). Yet, PTU-treated embryos manifested heterotaxy defects, and PTU was shown to directly adversely affect ciliary movement (van Veenendaal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we observed that administration of PTU during organogenesis caused delayed neural tube closure in E10.5 murine embryos, but these defects were not seen at the end of gestation (Benavides et al., ). In frog embryos, very early exposure to PTU results in heterotaxy defects (van Veenendaal et al., ). Despite widespread ATD use in pregnancy, formal studies of teratogenicity, similar to those required by the U.S. Food and Drug Administration (ICH S5(R2)), have yet to be performed (Wise, ).…”
Section: Introductionmentioning
confidence: 99%
“…Still, some studies have been negative (16,17), and until recently, the additional risk of birth defects after early pregnancy use of MMI/CMZ was considered to be very low (2,3). PTU was considered not to be teratogenic (2,3), even if some non-human studies were positive (18,19). However, two recent large controlled studies have shown that the risk is not negligible (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…acetyl]-L-al-anyl-2-phenyl]glycine-1,1-dimethylethyl ester; Sigma-Aldrich #05942) was dissolved in DMSO and used at 100-200M (Myers et al, 2014). PTU (Propylthiouracil; Sigma-Aldrich #1578000; 10mM stock stored at -80°C for long term and -20°C for short term) was dissolved in Ultrapure water (ThermoFisher #10977035) and used at 1mM (Veenendaal et al, 2013). Rapamycin (Sigma-Aldrich #37094) was dissolved in DMSO and used at 100nM.…”
Section: Drug Treatments Of Xenopus Embryosmentioning
confidence: 99%